2007
DOI: 10.1007/s11259-007-9007-9
|View full text |Cite
|
Sign up to set email alerts
|

Avermectin transepithelial transport in MDR1- and MRP-transfected canine kidney monolayers

Abstract: Fluxes of the anti-parasitic agents, [(3)H]-ivermectin, [(3)H]-selamectin and [(3)H]-moxidectin were studied across non-transfected and transfected canine kidney epithelial monolayers, MDCK II/wt, MDCK II-MDR1, MDCK II-MRP1 and MDCK II-MRP2. All four lines surprisingly expressed significant levels of P-glycoprotein (P-gp), coded for by MDR1, but MDCK II-MDR1 expressed increased levels compared to the other lines. MDCK II-MRP1 and MDCK II-MRP2 expressed increased levels of MRP1 and MRP2 respectively. Fluxes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…Competition for MDR1/Mdr1 function by ivermectin (K i 0.24 mM) correlates with peak plasma ivermectin concentrations found in man (0.05-0.1 mM), suggesting that kinetics in these in vitro models may be relevant to in vivo exposure levels (Ottesen and Campbell, 1994;González Canga et al, 2008). Brayden and Griffin (2008), found that there was no significant MRP-1-or MRP-2-mediated avermectin transport in the presence of functional MDR1. As with doxorubicin and vincristine, which are substrates for multiple transporters (Fung and Gottesmann, 2009), however, overlapping substrate specificity between MDR1 and MRP isoforms may provide an alternative route of efflux for these avermectins if MDR1/Mdr1 were inhibited.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Competition for MDR1/Mdr1 function by ivermectin (K i 0.24 mM) correlates with peak plasma ivermectin concentrations found in man (0.05-0.1 mM), suggesting that kinetics in these in vitro models may be relevant to in vivo exposure levels (Ottesen and Campbell, 1994;González Canga et al, 2008). Brayden and Griffin (2008), found that there was no significant MRP-1-or MRP-2-mediated avermectin transport in the presence of functional MDR1. As with doxorubicin and vincristine, which are substrates for multiple transporters (Fung and Gottesmann, 2009), however, overlapping substrate specificity between MDR1 and MRP isoforms may provide an alternative route of efflux for these avermectins if MDR1/Mdr1 were inhibited.…”
Section: Discussionmentioning
confidence: 89%
“…These observations were extended when Lespine et al, (2007) showed that ivermectin, abamectin, doramectin, eprinomectin, and selamectin were potent inhibitors of rhodamine-123 dye efflux from porcine kidney epithelial cells transfected with either mouse Mdr1a or human MDR1. Equally, an increase in basolateral-to-apical flux of [ 3 H]-ivermectin and [ 3 H]-selamectin was found in monolayers of MDCKII-MDR1 cells compared to wildtype MDCKII; this was significantly reduced by the bilateral addition of the MDR1 inhibitor verapamil (100 mM), (Brayden and Griffin, 2008). The data presented in this paper show abamectin, emamectin and ivermectin competition for MDR1 and Mdr1a-mediated H33342 dye efflux comparable to CSA in both SH-SY5Y and N2a cell lines respectively, consistent with these avermectins being potential substrates for MDR1/Mdr1 in the CNS/blood brain barrier of both species.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been shown to be a good inhibitor of the human transporter (Imai et al, 2004). Ivermectin and selamectin are potent anthelmintic drugs that interact with other ABC transporters like P-glycoprotein (Griffin et al, 2005;Brayden and Griffin, 2008). In this article, both antiparasitic drugs were identified as new inhibitors of the bovine, mouse, and human ABCG2.…”
mentioning
confidence: 99%
“…Selamectin is an interesting structural intermediate, with only one sugar residue. It resembles ivermectin in terms of P-gp inhibition [33] and transport [70,71] but has a lower affinity for the transporter ( Table 1). On the basis of the different ability of doramectin and selamectin, that only differ structurally by one sugar unit, to compete with verapamil on P-gp [33], the data indicate that the second sugar unit plays an important role in the interaction with Pgp.…”
Section: B Interaction Of Mls With P-gpmentioning
confidence: 99%